2014
DOI: 10.1016/j.bjorl.2014.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of balloon sinuplasty in patients with chronic rhinosinusitis without polyposis

Abstract: Sinuplasty is effective in reducing symptoms and improving quality of life as a treatment option for chronic rhinosinusitis in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 15 publications
1
11
0
1
Order By: Relevance
“…Quantitative evaluation of studies without industry sponsorship or conflicts of interests was not possible, as only a single study met criteria for metaanalysis when those with possible financial conflicts of interest or industry support were excluded. 19 While the findings of this study are consistent with the above quantitative analysis, future research without industry support is needed to further evaluate this potential bias.…”
Section: Discussionsupporting
confidence: 74%
“…Quantitative evaluation of studies without industry sponsorship or conflicts of interests was not possible, as only a single study met criteria for metaanalysis when those with possible financial conflicts of interest or industry support were excluded. 19 While the findings of this study are consistent with the above quantitative analysis, future research without industry support is needed to further evaluate this potential bias.…”
Section: Discussionsupporting
confidence: 74%
“…have published the results of a controlled randomised study with 24 patients, where functional endoscopic dilatation sinus surgery was found to be as effective as ESS. In a prospective cohort study with 13 patients (24 sinuses of which only 10 were maxillary sinuses) published by Abreu et al ., no complications were reported and quality of life was improved as assessed by SNOT‐20. With the exception of a study by Tomazic et al ., where a surprisingly high failure rate was reported, encouraging results have been reported from different study groups.…”
Section: Discussionmentioning
confidence: 94%
“…This fits with the literature, which generally supports the safety of the procedure. 1012 In terms of narrative, one might expect a balloon procedure to be safer. However, vigilance is still required especially in cases of anatomical variance.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the literature supports balloon sinuplasty as a safe and effective procedure, and there are multiple other small studies supporting this. 1012…”
Section: Discussionmentioning
confidence: 99%